Use of Multidirectional Cranial Distraction Osteogenesis for Cranial Expansion in Syndromic Craniosynostosis - Sunaga, Ataru (Plast Reconstr Surg Glob Open, 2017)
Patients with syndromic craniosynostosis often require a large amount of cranial expansion to avoid intracranial hypertension, but the surgical procedure remains controversial. A patient of severe syndromic craniosynostosis with multiple bony defects and anomalous venous drainage at the occipital region was treated by multidirectional cranial distraction osteogenesis (MCDO) at the age of 8 months. Distraction started 5 days after surgery and ceased on postoperative day 16. The distraction devices were removed 27 days after completing distraction. After device removal, the increase of intracranial volume was 155 ml and the cephalic index was improved from 115.5 to 100.5. The resultant cranial shape was well maintained with minimal relapse at postoperative 9 months. In cases of syndromic craniosynostosis with multiple bony defects and/or anomalous venous drainage at the occipital region, expansion of the anterior cranium by MCDO is a viable alternative to conventional methods.